S-glutathionylation reactions in mitochondrial function and disease - Mailloux, Ryan J.; Willmore, William G. (Frontiers in Cell and Developmental Biology, 2014)
Mitochondria are highly efficient energy-transforming organelles that convert energy stored in carbon bonds into the universal energy currency ATP. The production of ATP by mitochondria is dependent on oxidation of nutrients and coupling of exergonic electron transfer reactions to the genesis of transmembrane electrochemical potential of protons. Electrons can also prematurely “spin-off” from the respiratory complexes and univalently reduce di-oxygen to generate ROS, an important signaling molecule that can be toxic at high concentrations. Production of ATP and ROS are intimately linked by the respiratory chain and the genesis of one or the other inherently depends on the metabolic state of mitochondria. Various control mechanisms converge on mitochondria to adjust ATP and ROS output in response to changing cellular demands. One control mechanism that has gained a high amount of attention recently is S-glutathionylation, a redox sensitive covalent modification that involves formation of a disulfide bridge between glutathione and an available protein cysteine thiol. A number of S-glutathionylation targets have been identified in mitochondria. It has also been established that S-glutathionylation reactions in mitochondria are mediated by the thiol oxidoreductase glutaredoxin-2 (Grx2). In the following review, emerging knowledge on S-glutathionylation reactions and its importance in modulation mitochondrial ATP and ROS production will be discussed. Major focus will be placed on Complex I of the respiratory chain since 1) it is a target for reversible S-glutathionylation by Grx2 and 2) deregulation of Complex I S-glutathionylation is associated with development of various disease states particularly heart disease. Other mitochondrial enzymes and how their S-glutathionylation profile is affected in different disease states will also be discussed.